PENGGUNAAN METODE SOQ DALAM PENENTUAN KUANTITAS PEMESANAN PERISHABLE PRODUCT UNTUK MEMINIMALKAN RETURN - Noviana Noviana; Retnani Dian Mudiastuti (Journal of Engineering and Management in Industrial System, 2014)
Abstract For products with short life cycle, associated high risk is on the inventory management of finished products. This research took case study on newspaper company in South Sulawesi, which was forced to minimize newspaper return in order to operate in a more eficient level in high competition environment. The aim of this research is to find out the factors that caused newspaper overstock, to count the optimal order quantity with SOQ method (Single Order Quantity) and to compare the new quantity order proposed with the existing method used by the company, in term of return and cost. The result showed that SOQ method could decrease the return and cost caused. On November 2013 and December 2013, there were Rp. 116.844.000 dan Rp 120.112.800 cost saved, and the return also pressed by 48.685 units on November 2013 and 49.795 units on December 2013